Сучасні тренди та концептуальні підходи до розуміння сутності поняття «національна безпека» - Загуменна, Ю. О.; Zagumenna, Yu. O.; Юлія Загуменна (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 34-48, 2022)
Розглянуто у контексті існуючих наукових підходів сучасні тренди, що диктують смислове поняття «національна безпека». Продемонстровано тенденції розвитку вітчизняної, насамперед правової думки, яка точиться навколо поняття «національна безпека України». Акцентовано на провідній ролі юриспруденції в інтеграції наукових знань щодо проблематики національної безпеки. Визначено шляхи та перспективи вдосконалення нормативно-правового забезпечення національної безпеки в сучасних умовах розвитку Української держави.

In the context of existing scientific approaches, modern trends that dictate the semantic load of the concept of “national security” have been considered. The development trends of the national, first of all, legal debate surrounding the concept of “national security of Ukraine” have been demonstrated. Attention has been focused on the leading role of jurisprudence in the integration of scientific knowledge regarding national security issues. The novelty of the research consists in the formulation of a number of conclusions of both theoretical and practical nature, which should serve as a basis for determining through the prism of modern theoretical jurisprudence and national security science the phenomenon of national security on the example of modern Ukraine, improving its normative and organizational component. Under national security, the protection of the vital interests of the individual, society and the state, legal and social values, and the way of life from a wide range of external and internal threats, different in nature, has been considered. More specific varieties of the legal definition of “security”, which correlate with it as “general” and “special” categories, are the concepts of “national security”, “state security”, “public security”, “personal security”, and derivatives from them, such as “military security”, “economic security”, “information security” and other types of security, are allocated in a separate type in numerous scientific works of Ukrainian and foreign specialists depending on the object of protection, the sphere of social relations, and the types of practical activities of various state bodies. The ways and prospects of improving the regulatory and legal provision of national security in modern conditions of Ukraine’s development have been determined. The issue of legal reform in the field of national security has gained further improvement, namely, that it provides planned, scientifically based, socially acceptable and justified changes: 1) in legislation that guarantees national security and protects national interests; 2) in the structure, organization and activity of state authorities and other entities responsible for ensuring national security, in the system of their functions and powers, as well as in the ways (forms, methods) of their implementation; 3) in the qualitative strengthening of the state of security of the entire array of social relations, centered around national security and covered by the object of the reform, from external and internal, real and potential threats. Therefore, the reform of national security appears in the unity of three components: normative and legal (regulatory), management (subject) and object (change in the sphere of social relations in the field of national security).

Рассмотрены в контексте существующих научных подходов современные тренды, диктующие смысловое понятие национальной безопасности. Продемонстрированы тенденции развития отечественного, прежде всего правового мнения, которое идет вокруг понятия «национальная безопасность Украины». Акцентировано на ведущей роли юриспруденции в интеграции научных знаний по проблематике национальной безопасности. Определены пути и перспективы усовершенствования нормативно-правового обеспечения национальной безопасности в современных условиях развития Украинского государства.
Modern trends and conceptual approaches to understanding the essence of the concept of “national security”
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; національна безпека; national security; национальная безопасность; державна політика; state policy; государственная политика; безпекові правовідносини; security legal relations; правоотношения безопасности; правовий режим; legal regime; правовой режим; війна; war; война; збройна агресія; armed aggression; вооруженная агрессия; воєнний стан; martial law; военное положение; законодавство; legislation; законодательство